Listen (London : Melrose Film Productions, 1988)
Everyone needs to listen to do their work effectively - managers, sales people, technical experts, customer contact staff. There is hardly a department in your organisation which wouldn't benefit from this film
Bibliographical information is taken from the publisher's catalogue
Backup available in VHS
Keywords: Communication in management